2021
DOI: 10.3390/ijerph18115549
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of COVID-19 Lockdown in Italian Children and Adolescents with Type 1 Diabetes Mellitus: The Role of Separation Anxiety

Abstract: In March 2020, the Italian Government imposed mandatory home confinement to limit the spread of COVID-19. Few studies assessed the psychophysical impact of COVID-19 on chronically ill children. This study examined these effects on children with Type 1 Diabetes Mellitus (T1D) and their caregivers. Seventy-one patients (7–13 years) with T1D and their caregivers were administered a survey created ad hoc and some standardized questionnaires, assessing psychological well-being and anxiety. Medical data (physical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…As to the children, patients with cancer did not significantly differ from healthy peers in COVID-19-related worries, general psychological functioning, and anxiety symptoms, in line with the literature that reports unchanged psychological functioning for children with chronic diseases such as diabetes and asthma in the first lockdown [13,14]. A study on Dutch children with cancer observed no differences in health-related quality of life and fatigue between the pre-and early-COVID-19 periods; authors referred to children's experience in dealing with medical traumatic events and adequate care and support received to explain these results [38].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…As to the children, patients with cancer did not significantly differ from healthy peers in COVID-19-related worries, general psychological functioning, and anxiety symptoms, in line with the literature that reports unchanged psychological functioning for children with chronic diseases such as diabetes and asthma in the first lockdown [13,14]. A study on Dutch children with cancer observed no differences in health-related quality of life and fatigue between the pre-and early-COVID-19 periods; authors referred to children's experience in dealing with medical traumatic events and adequate care and support received to explain these results [38].…”
Section: Discussionsupporting
confidence: 86%
“…Scarce and inconsistent literature is available about the interplay between COVID-19-related worries and separation anxiety in chronically ill children. Italian studies on diabetic children report normative levels of psychological symptoms, but an increase in children's separation anxiety symptoms during the first lockdown, also associated with higher perceived fear of COVID-19 infection [13]. No differences in psychological functioning emerged when comparing Italian asthmatic children to their healthy peers during the first lockdown, except for higher worry about COVID-19 contagion.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Children with type 1 diabetes mellitus are another unique population. During lockdown, they had evident mood deterioration and required a higher daily total insulin dose, making glycemic control challenging [ 11 , 20 ]. However, the net effect on body weight or BMI could not be demonstrated in our analysis.…”
Section: Discussionmentioning
confidence: 99%